2020
DOI: 10.1021/acsabm.0c00300
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Decorated Nanoscale ZIF-8 with High Curcumin Loading Effectively Inactivates Gram-Negative and Gram-Positive Bacteria

Abstract: Bacteria-mediated infectious diseases have become a health-care challenge globally since the development of antibiotic resistance. Reactive oxygen species produced by photosensitizers have great potential in fighting bacterial infections, especially against Gram-negative bacteria that are hard to kill by regular methods owing to their formidable defensive membrane structures under the premise of avoiding overuse of antibiotics. In this work, a small molecular photosensitizer, curcumin (CCM), was used as a mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…The synthesis of GOx-encapsulated ZIF-8 (GOx@ZIF-8) NPs was similar to that of ZIF-8 NPs, where GOx was mixed with 2-MIM and 8-arm-PEG-OH before adding Zn-(NO 3 ) 2 . 20,33,36,37 SEM (Figure 3a) and TEM (Figure 3b) images showed that the average diameter of dodecahedral GOx@ZIF-8 NPs coated with TA/Fe 3+ was about 250 nm, which was similar to that of ZIF-8 NPs prepared in the absence of GOx (Figures S1d and S3). Due to the high adhesion of TA to ZIF-8 NPs, MPN shells were easily formed on the surface of GOx@ZIF NPs, which resulted in the increased surface roughness (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…The synthesis of GOx-encapsulated ZIF-8 (GOx@ZIF-8) NPs was similar to that of ZIF-8 NPs, where GOx was mixed with 2-MIM and 8-arm-PEG-OH before adding Zn-(NO 3 ) 2 . 20,33,36,37 SEM (Figure 3a) and TEM (Figure 3b) images showed that the average diameter of dodecahedral GOx@ZIF-8 NPs coated with TA/Fe 3+ was about 250 nm, which was similar to that of ZIF-8 NPs prepared in the absence of GOx (Figures S1d and S3). Due to the high adhesion of TA to ZIF-8 NPs, MPN shells were easily formed on the surface of GOx@ZIF NPs, which resulted in the increased surface roughness (Figure 3c).…”
Section: ■ Results and Discussionmentioning
confidence: 58%
“…Intermolecular hydrogen bonds between the phenolic hydroxyl group in ABE and the nitrogen atoms in 2‐methylimidazole cause this encapsulation. [ 39 ] Peak locations in UV–visible spectra are primarily influenced by particle shape and medium dielectric constant, implying polydispersibility of synthesized ABE@ZIF‐8 NPs, whereas the shape of the UV–visible peak determines the morphology of nanoparticles. The broad and asymmetrical surface plasmonic (SPR) bands indicate that the synthesized nanoparticles are anisotropic, while the narrowband indicates that the nanoparticles are spherical‐hexagonal.…”
Section: Resultsmentioning
confidence: 99%
“…The LbL coating approach applied here has previously been used to develop functionalized nanoparticles primarily for applications in cancer. [59][60][61] LbL has also been applied to NP coatings for antibacterial applications, mainly aimed at eliminating planktonic bacteria or preventing biofilm formation, 62,63 with a limited investigation of biofilm eradication. 64 In this work, we combined the LbL coating of bacteria-responsive polymers with a bacteria-responsive NP core and investigated both biofilm prevention and eradication effects.…”
Section: Characterizing Np Physicochemical Propertiesmentioning
confidence: 99%